LEARNING MODELS STARTING WITH BRAIN GYM IN LEARNING ENGLISH VOCABULARY AT ELEMENTARY SCHOOL - Amalia, Yahya (Institut Agama Islam Negeri Palopo, 2016)
Teaching English Vocabulary to the elementary school students is a challenge. Children in age ten to age 15 are in critical period. In this period they can get the lesson easily if they have good motivation to study especially in studying English. In elementary school, the teacher should have a good creativity in order to handle the class very well.Â The teacher should find some strategies to make the students keep concentrating on the lesson.Â In addition, the main role of teacher is to make their students motivated in learning. This article is aimed at explaining Learning Model Starting with Brain Gym in Learning English Vocabulary at Elementary School. Brain gym is a simple movement which involves some points which is related to the brain of human. It can make the students easily to breath, the blood circular can be in a good circulation.Â The movement of brain gym can increase the studentsâ concentration in learning, strengthen the studentsâ motivation, develop the studentsâ self confidence, self esteem, and togetherness feeling and can reduce the studentsâ stress in learning